PREDICATION OF FAILED BANKS AN EARLY WARNING MODEL APPLIED FOR THE COMMERCIAL BANKS IN THE SUBPRIME CRISIS - Qiu, Tianliang (2009)
Corporate failures always attract attention from governments and academics. From 2006 to 2008, I investigate the commercial banks in the recent world financial crisis. The Logit model I adopted indicates a good discriminant model to differentiate the problematic banks from the non-problematic counterparts, indeed the predictive value measured by ROC analysis one year prior to 2008 reaches to approximately 90%. This result suggests the Logit model used by academics to predict previous bank failures is also applicable for the current bank failures. Several causes of problem or failed banks have been studied in this paper. Capital adequacy, asset quality, earning performance and liquidity risk are the four main factors which contribute to failures of banks. This paper shows that several factors are significant of a bank’s survival status, at the 5 percent significance level, although several proxies used for these determinants do not conform to a priori expectations of the Human Information Processing theory, especially for the signs.